Stability-indicating RP-HPLC method development and validation for simultaneous estimation of bisoprolol fumarate and amlodipine besylate in bulk and in tablet dosage form - Rameshwar Bhausaheb Gholve, Sanjay Sudhakar Pekamwar, Tukaram Mohanrao Kalyankar (Journal of Applied Pharmaceutical Science, 2021)
A novel chromatographic method has been developed with a stability-indicating feature for simultaneous estimation of bisoprolol fumarate (BSL) and amlodipine besylate (AMD) in bulk and in tablet dosage form with minimized drug extraction steps. The chromatographic analysis was executed by the isocratic elution mode using Oyster ODS3 (150 × 4.6 mm, 5 μm) column (Merck & Co.) as the stationary phase at ambient temperature (about 25°C) with 1.0 ml/minute flow rate and 20 mM phosphate buffer with pH 2.5 (adjusted by 5% orthophosphoric acid):methanol:acetonitrile (42:29:29, v/v/v) as eluents at a wavelength of 230 nm. The retention time was found to be 2.543 and 4.883 minutes for bisoprolol and amlodipine, respectively. The method was found to be linear in the concentration range of 60.08– 140.19 μg/ml for BSL and 59.73–139.37 μg/ml for amlodipine with squared correlation coefficient (R2) of 0.999 in both cases. Individual drug substances and their combination drug product were exposed to conditions like acid, alkali, oxidative, thermal, photolytic, and humidity degradation; the degradation peaks were well separated from active analyte peaks. The acid-, alkali-, thermal-, and photolytic-induced stress studies signified the formation of a variety of degradants. Hence, it is recommended that BSL and AMD drug substances, as well as drug products, should be stored in tightly closed container protected from light and heat. The method was validated for specificity, linearity, quantitation limit, detection limit, accuracy, precision, robustness, and solution stability as per International Conference on Hormonization (ICH) guidelines and effectively used for regular analysis.
Keywords: RP-HPLC, bisoprolol, amlodipine, forced degradation, solution stability, validation